The correlation of the morphology of the medial patellofemoral ligament (MPFL) with the dimensions of the patella, the patellar tendon, the q-angle and femoral trochlear groove - Henning, Willem Johannes (University of the Free State, 2017)
The medial patellofemoral ligament (MPFL) is an essential contributing component to a stable patellofemoral joint (PFJ). The PFJ is a complex structure that has balanced forces acting on the stable joint. The aim of this study was to correlate the morphology of the MPFL with the Q-angle, the patellar tendon, the patella and the femoral trochlear groove (FTG) in a stable PFJ. Thirty-four cadaver knees were dissected. The Q-angle for each knee was measured with a goniometer. Dimensions of the MPFL, patella and patellar tendon were measured with a Vernier calliper. The femoral trochlear groove was photographed and photometrically measured with the use of the computer program ImageJ. The data collected were statistically analysed to determine Spearman’s Rank correlations coefficient (rs). A correlation coefficient of rs = 0.482 was considered significant. Firstly, it was found that the length of the MPFL correlated with eleven other measurements. These correlations include the proximal width of the patellar tendon; the length of the patellar tendon; the medial facet width of the patella; the articulating height of the patella; the osseous length of the patella; all the osseous measurements of the FTG; and the mathematically-derived depth of the FTG. Secondly, eight correlations were found with the femoral attachment width of the MPFL. These correlations include both the proximal and distal widths of the patellar tendon; the osseous length and width of the patella; the lateral patellar groove width of the FTG; both the medial and lateral altitudes of the FTG; and the altitude of the deepest point of the FTG. Lastly, the width of the attachment of the MPFL to the vastus intermedius tendon only correlated with the length of the patellar tendon. The morphology of the MPFL positively correlated with specific measurements of the patella, patellar tendon and the FTG in a stable PFJ. This may be explained by the gradual increase in size of the structures in the joint. The findings suggest that the MPFL forms part of a harmonious interplay and disrupting this balance, either by pathology or reconstructive surgery, may alter the delicate harmony in the joint.

Die mediale patellofemorale ligament (MPFL) is ’n noodsaaklike bydraende faktor tot ’n stabiele patellofemorale gewrig (PFG). Die PFG is ’n komplekse struktuur met gebalanseerde kragte wat saamwerk tot ’n stabiele gewrig. Die doel van hierdie studie was om die morfologie van die MPFL te korreleer met die Q-hoek, die patellêre tendon, die patella en die femorale trogleêre groef (FTG) in ’n stabiele PFG. Vier-en-dertig kadawerknieë is gedissekteer. Die Q-hoek van elke knie is gemeet met ’n goniometer. Afmetings van die MPFL, patella en patellêre tendon is gemeet met ’n Vernier skuifpasser. Die femorale trogleêre groef is gefotografeer en fotometries gemeet met die rekenaarprogram ImageJ. Die data versamel is statisties geanaliseer om die Spearman Rangkorrelasie koëffisiënt (rs) te bepaal. ’n Korrelasie koëffisiënt van rs = 0.482 is as beduidend beskou. Eerstens het die lengte van die MPFL gekorreleer met elf ander afmetings. Hierdie korrelasies sluit in die proksimale wydte van die patellêre tendon; die lengte van die patellêre tendon; die mediale faset-wydte van die patella; die artikulerende hoogte van die patella, die ossale lengte van die patella; al die osseuse afmetings van die FTG; en die wiskundig afgeleide diepte van die FTG. Tweedens is agt korrelasies gevind met die femorale hegtingswydte van die MPFL. Hierdie korrelasies sluit in beide die proksimale en distale wydtes van die patellêre tendon; die ossale lengte en wydte van die patella; die laterale patellêre groefwydte van die FTG, beide die mediale en laterale lengtes van die FTG; en die hoogte van die diepste punt op die FTG. Laastens het die wydte van die hegting van die MPFL tot die vastus intermedius tendon slegs met die lengte van die patellêre tendon gekorreleer. Die morfologie van die MPFL het positief gekorreleer met spesifieke afmetings van die patella, patellêre tendon en die FTG in ’n stabiele PFG. Dit kan moontlik verduidelik word deur die geleidelike toename in die grootte van strukture in die gewrig. Die bevindinge blyk daarop te dui dat die MPFL deel uitmaak van ’n interne harmonieuse wisselwerking en dat die ontwrigting van hierdie balans, hetsy deur patologie of rekonstruktiewe chirurgie, die delikate balans in die gewrig mag ontwrig.
Dissertation (M.Med.Sc. (Anatomy and Cell Morphology))--University of the Free State, 2017
Keywords: Stability; Patella; Q-angle; Medial patellofemoral ligament; Patellofemoral joint; Patellar tendon; Femoral trochlear groove; Spearman’s ranked correlation coefficient; Bones -- Joints